Enfermeiro navegador em oncologia: scoping review - Anjos, Thayane Ribeiro dos (2023)
Patient navigation emerged in the context of oncology, focused essentially on overcoming the barriers that affect health care. In this sense, there is the role of the nurse navigator who can favor, mainly, the patient, in the different stages that make up the care. Taking into account the impact caused by the exercise of this professional, associated with the need for more scientific production on the subject, a review was carried out in order to search for research that shows the activities that are performed by the nurse navigator in oncology. It should be noted that in order to expand the scientific evidence, the Scoping Review method was chosen based on the model proposed by the Joanna Briggs Institute (JBI). In view of this, searches were carried out between february 2023 to april 2023 in the PubMed/MEDLINE, LILACS, Scopus, Cochrane Library, Web of Science, Embase databases and in the gray literature through the CAPES catalog of theses and dissertations and the Oncology Nursing Society website. Documents that presented full texts available online in Portuguese, English or Spanish and that were focused on the research question, without applying a time limit, were highlighted. Thus, seven studies were selected to be read in full. With the analysis of the documents, it was observed that the period of publication of the studies was considerably recent. It was possible to verify the existence of articles that portrayed the application of interventions, in addition to reviews, qualitative research, and exclusive study for paper delineation. It was noted the description of activities corresponding to the navigation of patients performed by the nurse and also the results achieved with the assistance of this professional. Thus, it can be concluded that the evidence about the activities developed by nurses in the navigation of cancer patients, such as minimizing individual barriers related to care, favoring access to information, and facilitating symptom control, were remarkable. However, it remains relevant to highlight the low amount of scientific production on the subject, which points to the need for further studies in the area.